CCN1 Promotes Inflammation by Inducing IL-6 Production via α6β1/PI3K/Akt/NF-κB Pathway in Autoimmune Hepatitis - Jiang, Renquan; Tang, Jifeng; Zhang, Xuehao; He, Yujue; Yu, Ziqing; Chen, Shuhui; Xia, Jinfang; Lin, Jinpiao; Ou, Qishui (Frontiers in Immunology, 2022)
Autoimmune hepatitis (AIH) is a chronic inflammatory liver disease with unknown etiology. CCN1, an extracellular matrix-associated protein, is associated with carcinoma, inflammation, liver fibrosis, and even autoimmune diseases. However, the role that CCN1 plays in AIH has remained undetermined. In this study, expression of CCN1 in liver was detected by real-time PCR, western blot and immunohistochemistry (IHC). CCN1 level in serum was detected by ELISA. Diagnostic value of CCN1 was determined by receiver operating characteristic (ROC) curve analysis. CCN1 conditional knockout (CCN1fl/flCre+) mice were generated by mating CCN1fl/fl C57BL/6J and CAG-Cre-ERT C57BL/6J mice. Autoimmune hepatitis mice model was induced by concanavalin A (ConA). IKKα/β, IκBα, NF-κB p65 and Akt phosphorylation were determined by western blot. NF-κB p65 nuclear translocation was examined by immunofluorescence. Here, we found that CCN1 was over-expressed in hepatocytes of AIH patients. CCN1 level also increased in serum of AIH patients compared to healthy controls (HC). ROC curve analysis results showed that serum CCN1 was able to distinguish AIH patients from HD. In ConA induced hepatitis mice model, CCN1 conditional knockout (CCN1fl/flCre+) attenuated inflammation by reducing ALT/AST level and IL-6 expression. In vitro, CCN1 treatment dramatically induced IL-6 production in LO2 cells. Moreover, the production of IL-6 was attenuated by CCN1 knockdown. Furthermore, we showed that CCN1 could activate IL-6 production via the PI3K/Akt/NF-κB signaling pathway by binding to α6β1 receptor. In summary, our results reveal a novel role of CCN1 in promoting inflammation by upregulation of IL-6 production in AIH. Our study also suggests that targeting of CCN1 may represent a novel strategy in AIH treatment.